2016
DOI: 10.3748/wjg.v22.i41.9117
|View full text |Cite
|
Sign up to set email alerts
|

Altered pattern of tumor necrosis factor-alpha production in peripheral blood monocytes from Crohn's disease

Abstract: AIMTo evaluate the inflammatory state in Crohn’s disease (CD) patients and correlate it with genetic background and microbial spreading.METHODSBy means of flow cytometry, production of tumor necrosis factor-alpha (TNF-α) was measured in peripheral blood monocytes from patients suffering from CD, ulcerative colitis (UC) and in healthy subjects after stimulation of the NOD2 and TLR pathways. CD patients were genotyped for the three most common NOD2 variants (R702W, G908R and L1007Pfs*2) and basal production of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…[33][34][35] It was shown that peripheral monocytes from patients with CD have higher basal production of TNF-α regardless of NOD2 genotype and without a clear correlation with disease activity. 36 There are also reported cases of granulomatous vulvitis with occasional lymphangiectasia secondary to CD. [37][38][39] In this case, emphasis should be given to the cooccurrence of the ectatic lymphatic vessels and granulomatous inflammation that is notably associated with CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] It was shown that peripheral monocytes from patients with CD have higher basal production of TNF-α regardless of NOD2 genotype and without a clear correlation with disease activity. 36 There are also reported cases of granulomatous vulvitis with occasional lymphangiectasia secondary to CD. [37][38][39] In this case, emphasis should be given to the cooccurrence of the ectatic lymphatic vessels and granulomatous inflammation that is notably associated with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphostasis in CD may lead to poor clearance of antigen, localized immune dysfunction, and persistent inflammation which may contribute to stimulation of macrophages to proliferate and aggregate in the lymphatic vessels, where tumor necrosis factor (TNF) alpha may play a crucial role in intralymphatic “histiocytic” immunopathogenesis 33‐35 . It was shown that peripheral monocytes from patients with CD have higher basal production of TNF‐α regardless of NOD2 genotype and without a clear correlation with disease activity 36 . There are also reported cases of granulomatous vulvitis with occasional lymphangiectasia secondary to CD 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with clinical studies suggesting that MN‐derived TNF‐α and IL‐1β are high‐level drivers of intestinal inflammation in IBD. [ 110,111 ] We showed that iDCs properly matured, underwent activation, and exhibited apical antigen sampling functions, as inflammatory stimuli induced higher levels of GM‐CSF in IEB model‐iDC co‐cultures (Figure 6b‐iii). Such proper maturation and activation of iDCs has been shown to initiate subsequent T cell‐driven inflammatory responses in the onset of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that circulating monocytes of patients with CD produce more TNFα than healthy volunteers or patients with UC. [11] Although it is anticipated that greater production of TNFα may be associated with the behavior of CD and refractoriness to treatment, such data are not published. To this end, only indirect evidence is available.…”
Section: Discussionmentioning
confidence: 99%